RESEARCH AND FORECASTING OF PERFORMANCE INDICATORS OF HOUSING AND COMMUNAL SERVICES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In a rapidly changing economic and social environment, the importance of effective management of housing and communal services (HCS) becomes especially relevant. The work is aimed at studying key performance indicators of the housing and communal services sector, such as the level of quality of services provided, the financial stability of enterprises, energy saving and resource management. Particular attention is also paid to forecasting these indicators using mathematical modeling and data analysis methods, which makes it possible to assess the prospects for the development of the sector and identify potential risks. The results of the work can be used to optimize management processes, improve the quality of services and the sustainability of financial flows in the housing and communal services sector, which helps improve the quality of life of the population and the sustainable development of urban infrastructure.